2017
DOI: 10.3748/wjg.v23.i22.3945
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding with the artificial heart: Gastrointestinal hemorrhage in CF-LVAD patients

Abstract: Continuous-flow left ventricular assist devices (CF-LVADs) have significantly improved outcomes for patients with end-stage heart failure when used as a bridge to cardiac transplantation or, more recently, as destination therapy. However, its implantations carries a risk of complications including infection, device malfunction, arrhythmias, right ventricular failure, thromboembolic disease, postoperative and nonsurgical bleeding. A significant number of left ventricular assist devices (LVAD) recipients may exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 64 publications
0
47
0
1
Order By: Relevance
“…It is cleaved by ADAMTS-13, glycosylated and cleared from the bloodstream with a half-life of 12-20 h. 25 The mechanical forces of aortic stenosis, left ventricular assist device, and extracorporeal membrane oxygenation can easily shear and deform the high molecular weight multimers into smaller fragments, which impairs thrombosis and interferes with platelet aggregation. 26,27 von Willebrand factor fragmentation may, by itself, be pro-angiogenic and potentially involved in GI hemorrhage in these severe settings. 26,28 Cross-sectional imaging Cross-sectional imaging techniques for evaluation of the small bowel include helical computed tomography enterography/enteroclysis (CTE), helical CT angiography, and magnetic resonance enterography/enteroclysis (MRE).…”
Section: --mentioning
confidence: 99%
See 1 more Smart Citation
“…It is cleaved by ADAMTS-13, glycosylated and cleared from the bloodstream with a half-life of 12-20 h. 25 The mechanical forces of aortic stenosis, left ventricular assist device, and extracorporeal membrane oxygenation can easily shear and deform the high molecular weight multimers into smaller fragments, which impairs thrombosis and interferes with platelet aggregation. 26,27 von Willebrand factor fragmentation may, by itself, be pro-angiogenic and potentially involved in GI hemorrhage in these severe settings. 26,28 Cross-sectional imaging Cross-sectional imaging techniques for evaluation of the small bowel include helical computed tomography enterography/enteroclysis (CTE), helical CT angiography, and magnetic resonance enterography/enteroclysis (MRE).…”
Section: --mentioning
confidence: 99%
“…26,27 von Willebrand factor fragmentation may, by itself, be pro-angiogenic and potentially involved in GI hemorrhage in these severe settings. 26,28 Cross-sectional imaging Cross-sectional imaging techniques for evaluation of the small bowel include helical computed tomography enterography/enteroclysis (CTE), helical CT angiography, and magnetic resonance enterography/enteroclysis (MRE). 5 In an emergency, dynamic or enhanced helical CT without enterography/enteroclysis provides important information regarding mass lesions such as tumors, inflammation, and vascular diseases, including arteriovenous malformation (AVM, Fig.…”
Section: --mentioning
confidence: 99%
“…Previous studies have suggested that the lowest chance of bleeding occurred in blood type A patients [12] and the highest in patients with history of GI hemorrhage prior to LVAD placement [11]. Furthermore, male gender and older age are recognizable risk factors [5]. There also seems to exist a possible correlation with GI hemorrhage in patients with easily observed nasal hypervascularity following LVAD implantation [13].…”
mentioning
confidence: 99%
“…Historically, up to 60% of LVAD recipients may develop gastrointestinal (GI) hemorrhage [5]-an important issue given increased prevalence of implantation worldwide. In fact, it is the most common adverse event in patients with post-device implantation [3] and typically resolves after a heart transplant [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation